2017
DOI: 10.1177/0192623317709091
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Di(n-butyl)phthalate Induces Morphological and Biochemical Changes in Rats Postpuberty

Abstract: Pregnant Sprague-Dawley rats were orally administered di( n-butyl)phthalate (DBP; 100 mg/kg/day) on gestation days (GD) 12 to 21. We investigated the male offspring and probed morphological alterations in Sertoli cells at 7, 9, 14, and 17 weeks of age. Parameters assessed in this study included offspring number, sex ratios, body weights, testis weights, seminiferous tubule (ST) profile numbers and diameters, number of vimentin-labeled Sertoli cells, and both testosterone and follicle-stimulating hormone (FSH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…This study is the first to examine body weight effects following developmental DBP exposure in mice, but studies in rats have also demonstrated mixed effects on offspring body weight 37 53 , 54 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This study is the first to examine body weight effects following developmental DBP exposure in mice, but studies in rats have also demonstrated mixed effects on offspring body weight 37 53 , 54 …”
Section: Discussionmentioning
confidence: 95%
“…This study is the first to examine body weight effects following developmental DBP exposure in mice, but studies in rats have also demonstrated mixed effects on offspring body weight. 37,53,54 This is the first animal study to examine the impact of developmental exposures to mixtures of phthalates on body weight. Exposure to phthalate mixtures did not appear to result in an exaggerated effect on PND21 body weight; females exposed to DEHP + DINP did not weigh significantly more than controls, and those exposed to DEHP + DINP + DBP weighed more than controls to a moderate degree of statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels have been detected in human urine, follicular fluid, and serum in different occupationally exposed groups [21,24]. In vitro and animal studies have shown that DBP disrupts the reproductive system resulting in inhibition of ovarian antral follicle growth and viability, altered gene expression in ovaries, testicular malformation and dysfunction, inhibition of spermatogenesis, and altered androgen signaling in males [2528]. In humans, a significant inverse relationship has been observed between levels of DBP metabolites (i.e.…”
Section: Introductionmentioning
confidence: 99%